2010
DOI: 10.1016/j.cemconcomp.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional change and elastic behavior of layered silicates and Portland cement paste

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Drying shrinkage of cement paste might have large impact on concrete property, because large shrinkage difference is expected in concrete and cracks in cement paste around aggregates are going to be produced under drying (Pickett 1956;Hansen and Nielsen 1965;Hobbs 1974;Grassl et al 2010;Idiart et al 2011;Lagier et al 2011;Zhang et al 2013;Maruyama and Sasano 2014), while the mechanism of shrinkage of hcp is not clarified (Powers 1965;Helmuth and Turk 1967;Feldman and Sereda 1968;Wittmann 1968;Bažant 1972;Beltzung and Wittmann 2005;Setzer 2007;Wittmann 2008;Beaudoin et al 2010;Maruyama 2010). The most lost part is irreversible shrinkage of hcp under the first desorption process.…”
Section: Cement Paste Properties Under the First Dryingmentioning
confidence: 99%
“…Drying shrinkage of cement paste might have large impact on concrete property, because large shrinkage difference is expected in concrete and cracks in cement paste around aggregates are going to be produced under drying (Pickett 1956;Hansen and Nielsen 1965;Hobbs 1974;Grassl et al 2010;Idiart et al 2011;Lagier et al 2011;Zhang et al 2013;Maruyama and Sasano 2014), while the mechanism of shrinkage of hcp is not clarified (Powers 1965;Helmuth and Turk 1967;Feldman and Sereda 1968;Wittmann 1968;Bažant 1972;Beltzung and Wittmann 2005;Setzer 2007;Wittmann 2008;Beaudoin et al 2010;Maruyama 2010). The most lost part is irreversible shrinkage of hcp under the first desorption process.…”
Section: Cement Paste Properties Under the First Dryingmentioning
confidence: 99%
“…However, studies have reported that hcp undergoes irreversible shrinkage after the first desorption process (Helmuth and Turk 1967;, indicating the occurrence of an irreversible reaction accompanied by a physical property change after drying. This irreversible reaction has been studied using various procedures, including nitrogen BET surface-area measurements (Hunt et al 1960;Parrott et al 1980;Litvan and Myers 1983;Maruyama et al 2014a), water-vapor BET surface-area measurements (Tomes et al 1957;Maruyama et al 2014a), and surface area and C-S-H structures obtained by small-angle X-ray or neutron scattering (Bayliss 1973;Winslow and Diamond 1974;Kropp et al 1985;Völkl et al 1987;Thomas et al 1998, Chiang et al 2012, 2013, among other techniques and interpretations (Feldman and Sereda 1968;Wittmann 1968, Parrott et al 1980Parrott and Young 1981;Beaudoin 1982;Jennings 2008;Beaudoin et al 2010;Maruyama 2010;Muller et al 2013). However, research efforts have largely ignored the strength of hcp and concrete during the initial drying and heating process.…”
Section: Introductionmentioning
confidence: 99%
“…The shrinkage mechanism of hardened cement paste is still under discussion, and several theories such as the surface energy theory, capillary tension theory, and disjoining (or hydration pressure) theory exist, with a combination of them having been proposed thus far (Powers 1965;Feldman and Sereda 1968;Wittmann 1968;Hansen 1987;Beaudoin et al 2010;Maruyama 2010). In addition to these theories, hardened cement paste under the first desorption process shows irreversible shrinkage due to colloidal alternation of C-S-H (Helmuth and Turk 1967;Maruyama et al 2015).…”
Section: Modulus Of Elasticity Shrinkage and Thermal Expansion Coefmentioning
confidence: 99%